Ancient Maya Pottery : Classification, Analysis, and Interpretation - Chase, Arlen F. (Arlen Frank), 1953-; Chase, Diane Z.; Aimers, James J. (Book collections on Project MUSE., 2013)
The ancient Maya produced a broad range of ceramics that has attracted concerted scholarly attention for over a century. Pottery sherds--the most abundant artifacts recovered from sites--reveal much about artistic expression, religious ritual, economic systems, cooking traditions, and cultural exchange in Maya society. Today, nearly every Maya archaeologist uses the type-variety classificatory framework for studying sherd collections. This impressive volume brings together many of the archaeologists signally involved in the analysis and interpretation of ancient Maya ceramics and rep.